ECONOMIC VALUATION OF JATILUWIH, PENEBEL TABANAN - Putu Ayu Meidha Suwandewi; Putu Novia Hapsari Ardianti (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
This research entitled "Economic Valuation of Jatiluwih, Penebel Tabanan". The purpose of this study was to determine the economic value of Jatiluwih are assessed using contingent valuation method and income approach. The variables used in this study is the willingness to pay as dependent variable and the travel cost, number of visits, income, education, age, quality, and presence or absence attractions substitution as independent variables. The data used in this research is the primary data in the form of questionnaire results from 100 respondents. Equipped also with secondary data which is the data on the number of foreign tourists and domestic visitors to the province of Bali and Tabanan regency in the last five years, as well as data on the number of visitors who visited attractions Jatiluwih in the last five years. Based on the results, the conclusion is that the economic value of Jatiluwih using contingent valuation method is Rp149.541.653.788,51 with the average value willingness to pay of domestic tourism is Rp24.705,88 per individual per visit and Rp. 46.774,00 per individual per year. Average value willingness to pay of foreign is Rp37.325,94 per individual per visit and Rp 37.325,94 per individual per year. The economic value of attractions Jatiluwih based on income approach is divided into two, that is the DCF based attractions Jatiluwih is Rp34.431.981.960,00 and DCF based productive land is Rp4.600.267.876.436.